2014
DOI: 10.1159/000366316
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Control of Trefoil Factor Family (TFF) Peptide Expression in Human Retinoblastoma Cell Lines

Abstract: Background: Recent studies demonstrated that epigenetic mechanisms are involved in the regulation of trefoil factor family (TFF) peptide expression in cancer. In human tissues with endogenous TFF1, TFF2 or TFF3 gene expression, the corresponding promoter is unmethylated and in organs without TFF expression, the promoter of the three genes is highly methylated. Methods: Retinoblastoma (Rb) cell lines were treated with the DNA methyltransferase inhibitor 5-Aza-2`deoxycytidine (5-Aza-dC), the histone deacetylase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
(78 reference statements)
1
18
0
Order By: Relevance
“…The loss of TFF1 in gastric cancer and its overexpression in ovarian cancer promote tumorigenesis involving the Wnt/ß‐catenin signaling pathway . Loss of TFF1 expression is epigenetically regulated by promotor methylation in gastric cancer and likewise in retinoblastoma cell lines as recently published by our group . The mechanisms by which TFF1 promotes apoptosis and changes proliferation behavior of tumor cells remain, however, largely unknown.…”
supporting
confidence: 51%
See 2 more Smart Citations
“…The loss of TFF1 in gastric cancer and its overexpression in ovarian cancer promote tumorigenesis involving the Wnt/ß‐catenin signaling pathway . Loss of TFF1 expression is epigenetically regulated by promotor methylation in gastric cancer and likewise in retinoblastoma cell lines as recently published by our group . The mechanisms by which TFF1 promotes apoptosis and changes proliferation behavior of tumor cells remain, however, largely unknown.…”
supporting
confidence: 51%
“…We performed TFF1 knockdown (KD) experiments in the RB cell line RBL30, exhibiting decently detectable endogenous TFF1 levels, to confirm TFF1 effects on growth and apoptosis. Testing different TFF1 ‐specific shRNA clones, we achieved a very efficient knockdown with an 80–95% reduction in TFF1 expression confirmed by quantitative Real‐time PCR (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group was the first to investigate retinal expression of TFF peptides. Previous studies by our group revealed that only TFF3, but not TFF1 and TFF2 are expressed in the healthy human retina [ 11 ; 12 ], whereby retinoblastoma (RB) cell lines, established from malignant eye tumors of children, exhibit high levels of TFF1 [ 11 ; 12 ], but only trace amounts of TFF3 and no detectable TFF2 . Most recently, we demonstrated that the expression of TFF3 in retinoblastoma cell lines is regulated epigenetically [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“… 42 , 46 Interestingly, deletions of some of these tumor suppressor genes may drive RB. 46 Moreover, high-density methylation of numerous other genes, such as TFF3 , 47 the apoptotic effector CASP8, 48 , 49 the DNA repair gene MLH1 , 50 APC-2 , 31 and the RB2/p130 gene, is involved in RB 51 , 52 ( Table 1 ).…”
Section: Dna Methylation In Ocular Tumorsmentioning
confidence: 99%